Investigation of the relationship between teachers’ inquiry-based teaching self-efficiency for STEM+S and their computational thinking skills - Başaran Mehmet; İlter Merve (Research on Education and Media)
This study examines the relationship between teachers’ inquiry-based teaching self-efficacy and computational thinking skills. The research was conducted in the survey model, which is the correlational model that reveals the relationship between two variables. The study sample comprised 369 teachers working in Gaziantep with different seniority and branches. Before the research, teachers were expected to receive a level of technology education that they could use in educational activities. The teachers who received technology training were given training on the computational thinking method. The conceptual states of computational thinking in education, the stages of computational thinking were given beforehand, and then, the teachers were expected to use the method with practical examples, where they could use their computational thinking skills. In this way, it was ensured that the teachers were aware of the computational thinking method and the target sample group was formed for this study. The data of the study were collected 1 month after this training. Data collection tools were the Inquiry-Based Teaching Self-efficacy scale and Computational Thinking Skills Scale. Correlation, regression, and multiple regression analyses were performed in the data analysis. Significant relationships were found between the scale’s subdimensions and total scores. When the relationship between the participants’ computing thinking skills scores and the inquiry-based teaching self-efficacy was examined, a moderate relationship was found between both variables.